Death of a ghost [large type] - Beaton, M. C. (Beaton, M. C. Hamish Macbeth mysteries., 2017)
Spending a night at the reputedly haunted Castle Drim, Hamish Macbeth and his partner, Charlie Carter, discover a dead body and a smuggler's drop and become determined to unravel the strange mystery before more bodies turn up.